(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article explores the effectiveness of teaching writing through a direct thinking approach without reliance on translation. It argues that encouraging learners to generate ideas directly in the target language promotes fluency, reduces interference from the first language, and develops authentic written expression. Using a theoretical-analytical framework, the study examines pedagogical principles, classroom strategies, and potential challenges associated with this approach. The findings suggest that direct thinking contributes to stronger writing competence, greater learner autonomy, and more natural language production when supported by appropriate instructional techniques.